Advanced Oxidation Process (AOP): Degradasi Zat Warna Rhodamin B Dengan Metode Fotokatalitik Menggunakan Katalis Covalent Triazine Framework (CTF) - Andes Sagita; Edy Saputra; Panca Setia Utama (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
BPS recorded the export value of national textile products reached US 13.22 billion in 2018 and increased to US 15.73 in 2019. The problem that later arises was the textile waste generated by those industries. One of the methods for treating textile dye waste is the photocatalytic. The catalyst used in this study is the Covalent Triazine Framework (CTF), while the radiation comes from a 250 watt mercury lamp. The dye waste used is rhodamine B. The CTF catalyst synthesis was carried out by the ionothermal method at a temperature of 450oC and argon atmosphere for 18 hours. 1,4-dicyanobenzene used as monomer and ZnCl2 as molten salt, the two ingredients are mixed in a furnace cup with a weight ratio of 1: 8 (monomer: molten salt). The best photocatalytic results were shown by variations in the concentration of 1 g/l catalyst and 10 ppm of rhodamine B with a degradation efficiency of 94.790%. Keywords: covalent triazine framework, ionothermal, textile, photocatalytic